2008
DOI: 10.1007/s10611-007-9089-x
|View full text |Cite
|
Sign up to set email alerts
|

Rent-seeking and economic governance in the structural nexus of corruption in China

Abstract: This article examines the sources of widespread rent-seeking practices and their relations to corruption in China. It argues that rent-creation and seeking are difficult to eliminate because they have become institutionalized as the constitutive parts of economic governance. Using case studies drawn from a number of industrial sectors, this study shows that the creation and allocation of economic rents has become a major policy instrument used by various levels of governments to manoeuvre industrial plans and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 15 publications
0
28
1
Order By: Relevance
“…Furthermore, according to Ngo (2008), economic rents are generated in China through the government's rationing of production licenses, fixing of prices and imposition of trade quotas with a view to effect industrial plans and development priorities. In his investigation of the links between rent-seeking, economic governance and corruption in China, Ngo's study concluded that rent-seeking is already intertwined with economic governance and it is being used in a corrupt way by agents of the government as they (the agents) collude with business handlers to accrue extra profits through bribery in areas such as construction works, property rights transfers, medical supplies, government procurements and exploration of natural resources.…”
Section: Corruption and Governancementioning
confidence: 99%
“…Furthermore, according to Ngo (2008), economic rents are generated in China through the government's rationing of production licenses, fixing of prices and imposition of trade quotas with a view to effect industrial plans and development priorities. In his investigation of the links between rent-seeking, economic governance and corruption in China, Ngo's study concluded that rent-seeking is already intertwined with economic governance and it is being used in a corrupt way by agents of the government as they (the agents) collude with business handlers to accrue extra profits through bribery in areas such as construction works, property rights transfers, medical supplies, government procurements and exploration of natural resources.…”
Section: Corruption and Governancementioning
confidence: 99%
“…In our study, we found that in China, market fragmentation and state intervention have led to significant rent-seeking activities (cf. Ngo, 2008).…”
Section: State Interventionmentioning
confidence: 99%
“…As a result, firms offer bribes to government officials in exchange for the creation and allocation of the rents. A great amount of rent-seeking opportunities thus bear directly on the prevalence of corruption/bribery in China (Ngo 2008). Thus, we propose the following hypothesis:…”
Section: Government Interventionmentioning
confidence: 90%
“…It is said that rent-seeking is one of the most common sources of corruption in today's China (Ngo 2008). The Chinese government uses various tools or policies to speed up economic growth, to boost exportion of goods and services, to adjust the distribution of incomes, to control price of commodities, and so on.…”
Section: Government Interventionmentioning
confidence: 99%
See 1 more Smart Citation